Solidification-stabilization of waste activated sludge from petroleum refinery - Omar, F.R.M. (2008)
The present study focuses on the solidification and stabilisation of waste activated sludge from petroleum refinery (Petrronas Penapisan Melaka Sdh. Bhd., Malaysia). Two cementitious materials, Pulverised Fly Ash (PFA) and Lime, were used along with ordinary Portland cement (OPC) to investigate the feasibility of solidifying and stabilising the sludge. The research studied the strength development and heavy metal (zinc) leaching of the final product (concrete). Unconfined compressive strength was tested and leaching was determined using the Toxicity Characteristic Leaching Procedure (TCLP). Over 92% immobilisation of zinc was obtained in all cases. Higher concrete strength was obtained with PFA than with Lime.